Control of subclinical bovine mastitis - Searcy, R.; Reyes, O.; Guajardo, G. (British Homeopathic Journal, 1995)
A clinical trial was conducted on a dairy farm. 26 animals were divided into 2 groups of 13 each, pairing on clinical and subclinical mastitis status, milk production and number of lactations, assigning both animals and treatments by a systematic random method. One group received homoeopathic treatment, the other placebo. Monthly milk production was carefully recorded for each animal, as were the results of the California Mastitis Test (CMT) performed on each quarter of the udder. The proportion of affected quarters according to CMT was 32% in the treated group, and 68% in the control group. The odds ratio of the difference shows that animals receiving placebo presented 4.5 (1.78–11.73) times more subclinical mastitis than those under homoeopathic treatment (p<0.05). Average milk production in the treated group did not differ significantly from that of the control group (p>0.05). The study confirms previous observations of the benefit the homoeopathic method can provide in disease control in animal populations.
Keywords: Homoeopathic mastitis control; Homoeopathic combinations; Bovine mastitis; Herd disease control; Homoeopathy in veterinary medicine; Subclinical bovine mastitis